H-NS mediates the dissociation of a refractory protein–DNA complex during Tn10/IS10 transposition - Liu, Danxu; Haniford, David B.; Chalmers, Ronald (Oxford University Press, 2011)
Tn10/IS10 transposition takes place in the context of a protein–DNA complex called a transpososome. During the reaction, the transpososome undergoes several conformational changes. The host proteins IHF and H-NS, which also are global regulators of gene expression, play important roles in directing these architectural changes. IHF binds tightly to only one of two transposon ends within the transpososome, folding this end into a DNA loop structure. Unfolding this DNA loop is necessary for excising the transposon from flanking donor DNA and preventing integration of the transposon into itself. We show here that efficient DNA loop unfolding relies on the continuity of the flanking donor DNA on the side of the transpososome opposite to the folded transposon end. We also show this same donor DNA is a preferred binding site for H-NS, which promotes opening of the IHF-loop, which is required for productive target interactions. This is counter to the usual mode of H-NS action, which is repressive due to its propensity to coat DNA. The interplay between IHF and H-NS likely serves to couple the rate of transposition to the host cell physiology as both of these proteins are integrated into cellular stress response pathways.